Design and Analysis of UWB MIMO Antenna for Smart Fabric Communications - Thennarasi Govindan; Sandeep Kumar Palaniswamy; Malathi Kanagasabai; Sachin Kumar (International Journal of Antennas and Propagation)
This paper presents a flexible multiple-input, multiple-output (MIMO) antenna with ultrawideband (UWB) performance for smart clothing applications. The MIMO antenna is comprised of four octagonal-shaped radiators with several slots loaded into them, and it offers a frequency range of 2.9–12 GHz. The unit cell has a size of 0.26λ0 × 0.164λ0 × 0.014λ0 and the MIMO antenna has a size of 0.48λ0 × 0.48λ0 × 0.014λ0, where λ0 corresponds to the lowest operating frequency. The radiation and diversity performances of the antenna are evaluated, and the obtained metrics are envelope correlation coefficient (ECC) <0.045, diversity gain (DG) >9.9 dB, total active reflection coefficient (TARC) <−14 dB, and channel capacity loss (CCL) <0.13 bits/s/Hz. The bending analysis of the MIMO antenna is performed. The specific absorption rate (SAR) of the MIMO antenna is also investigated, and the obtained values are 0.229 W/Kg (4 GHz), 0.253 W/Kg (7 GHz), and 0.463 W/Kg (10 GHz).